(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The productivity of the work force is the most decisive factor as faras the success of an organization is concerned. The productivity in turn isdependent on the psychosocial well-being of the employees. Stress can affectone‘s health, work performance, social life and the relationship with familymembers. The stress response is a complex emotion that produces physiologicalchanges to prepare us for fight or flight, to defend ourselves from the threator flee from it. The stressors and its consequences are to be understood atindividual and organizational level. Stress in the workplace has emerged as amajor issue for businesses and has reached alarming proportions. Organizationsmust develop stress prevention as well as stress reduction techniques. Thisstudy focuses on practices adopted by organizations to prevent, minimize and toovercome the stress. The study aims at understanding use of yoga, meditation,burn out and soothing humor by different organizations as an antidote toworkplace stress.